Conceptual framework on teaching capacitors and inductors - Erol, Mustafa; Ãƒâ€“nder, Esra Bilal (Momentum: Physics Education Journal, 2021)
The objective of this work is to suggest a conceptual framework on teaching capacitors and inductors in order to improve teaching abilities and to eliminate some fundamental misconceptions. The effort initially deals with resolution of physical structure and structural concepts/parameters of the devices and then resolves DC and AC responses of the inductors and capacitors. The resolutions are achieved by considering basic serious RL and RC circuits and resolving the circuits both theoretically and experimentally. As a result, an alternative teaching approach is offered and also a novel instructional material is developed and suggested. Some teaching clues are briefly inserted to guide teachers/instructors to reach a higher comprehension level. It is believed that the implications of the developed teaching material would be quite high and beneficial.